The Effect of Employee Training and Development on Employee Performance at PT FUMIRA - Badrun Badrun (International Journal Labs, 2026)
This research aims to determine how much impact employee training and development programs have on performance at PT Fumira. The method used in this research is associative quantitative, involving all PT Fumira employees as research subjects. Data is collected through surveys covering the entire population. In this research, data analysis was caried out using statistical techniques such as linear regression and t-tests, which were processed using IBM SPSS version 29.0 software. The research results show that the training program significantly improves employee performance, with a calculated t-value of 5.120 and a regression coefficient of 15.820. This means that whenever training is improved, employee performance also increases. Likewise, employee development shows a significant influence, with a calculated t-value of 4.773 and a regression coefficient of 32.603, indicating that the development program improves employee performance effectively. Furthermore, multiple regression analysis combining training and development shows that they together explain 79.8% of the variation in employee performance, with a calculated F value of 39.797 which is highly significant at a significance level of less than 0.001. The results of this research provide practical insight for PT Fumira to design and implement more effective training and development programs. These findings can also be a reference for other companies in the same industry who want to improve their employee performance through systematic and data-based training and development programs.